The Economic Condition of Older Adults in Goa - Siqueira Lobo, Charmaine Savia; Falleiro, Savio da Piedade (Arthshastra Indian Journal of Economics & Research, 2024)
Purpose : This study examined the household composition, income, spending, and financial dependency of older persons in Goa to determine their economic situation. The rapid aging population and its impact on older people’s financial situation made this study necessary. Methodology : A survey of 400 senior adults was conducted in six talukas in Goa using multistage sampling. Binary logistic regression, chi-square, and t-tests were used to examine the data. Using SPSS Software, the Young–Olds (60–74 years) and Old–Olds (75 and above) were compared. Findings : We found that the dependents in Old–Old households exceeded those in Young–Old households, leading to significant differences in household income and expenditure. The main sources of revenue were interest on deposits and retirement pensions, but the biggest expenses were related to food and health. The older women living in cities, with their low health status and high medical costs, were more likely to become financially dependent. Practical Implications : Age-friendly policies should be put in place, pensions should be reviewed on a regular basis, and Goa should create a special directorate for senior residents. Although this study is restricted to Goa, it offered a foundation for further extensive research in other states to address the financial difficulties older persons confront and improve existing procedures where they are deficient. Originality : In Goa, older adults are an understudied demographic. Since Goa is aging more quickly than the rest of India, this study, which is the first to examine their economic situation, closes a big gap and has important ramifications.